Wandycz, The Price Of Freedom - Gentry, Robert (Teaching History: A Journal of Methods, 1993)
Here is a book for students and instructors alike who lack the necessary historical context to make some sense of the often bewildering contemporary events occurring in the erstwhile Soviet Union and its satellites since the fall of the Berlin Wall and the apparent collapse of communism. Piotr Wandycz, Bradford Curfee Professor of History at Yale University and author of numerous works on Poland and East Central Europe, offers a crisp, readable survey of the history of East Central Europe since the middle ages without resorting to historical clichés, oversimplification, or national stereotypes. Within the compass of not quite 300 pages of text, he narrates the political and diplomatic history of the area and at the same time devotes considerable attention to the cultural, social, and economic developments that make the historical events understandable.